Effect of Roasting Temperature on Arabica Coffee Caffeine Content by UV-Vis Spectrophotometry (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Coffee is a major agricultural commodity in Indonesia, with caffeine as its principal bioactive compound influencing product quality and consumer health. Roasting affects caffeine levels, but data on its impact in locally produced Arabica coffee remain limited. This study evaluated the effect of roasting temperature on caffeine content in Arabica coffee beans from Pulosari District, Central Java, using UV-Visible spectrophotometry as a cost-effective alternative to HPLC. Coffee samples roasted at 200 °C, 210 °C, and 215 °C for nine minutes were analysed. Caffeine was extracted via reflux and sublimation, identified by thin-layer chromatography (TLC), and quantified using UV-Vis spectrophotometry. TLC confirmed caffeine presence in all samples with Rf values (0.65–0.66) matching the standard. The UV-Vis method showed excellent linearity (r = 0.9981), precision (RSD = 0.39%), accuracy (95.90–98.93%), and acceptable LOD (0.730 ppm) and LOQ (2.435 ppm). Caffeine content decreased significantly with increasing roasting temperature (p < 0.05), from 0.181% at 200 °C to 0.139% at 215 °C. These results demonstrate that roasting temperature significantly influences caffeine retention, and UV-Vis spectrophotometry is a reliable tool for caffeine quantification in small-scale coffee processing.